Epidemiological study of infection with intestinal protozoa: Cryptosporidium & Giardia & Eimeria in calves in Baghdad - Kawan, May H. (The Iraqi Journal of Veterinary Medicine, 2004)
A total of 250 fecal samples were collected from 1->30 days old calves, of both sexes suffered from diarrhea, from 3 different farms in Baghdad: Al-Ishaki 120 samples, Al Nasser 80 samples and 7 Nissan 50 samples. Three diagnostic methodes were used for each fecal sample for detection of single and mixed infection with intestinal protozoa: Cryptosporidium, Giardia and Eimeria: Modified Zehil Neelson stain and Ligol’s iodine stain and flotation technique with zinic sulphate solution for detection of Cryptosporidium oocysts, Giardia cysts and Eimeria oocysts respectively. This study recorded a total rate of infection with intestinal protozoa 37.6%, and rate of single & mixed infection in 3 farms 21.2% & 16.4% respectively. The total rate of single infection with Cryptosporidium, Giardia and Eimeria were 52.8%, 26.4% and 20.7% respectively. For mixed infection, this study recorded a total rate of double infection with Cryptosporidium & Giardia, Cryptosporidium & Eimeria and Giardia & Eimeria: 46.3%, 34.1% and 9.75% respectively, while a total rate of triple infection with 3 intestinal protozoa was 9.75% in 3 farms. The result of this study revealed the relation between ages, sexes of calves with single and mixed infection with intestinal protozoa. The highest number of calves with single infection with Cryptosporidium were 12 in age of 1-10 days, with Giardia 6 calves in age of each 21-30 and >30 days, and with Eimeria 10 calves with age of >30 days. For mixed infection, the highest number of calves with double infection by Cryptosporidium & Giardia, Cryptosporidium & Eimeria and Giardia & Eimeria: 10 calves in age of 21-30 days, 10 and 4 calves in age of >30 days respectively, while the highest number of calves infected with triple infection by three intestinal protozoa were 4 calves in >30 days of age. Sexes of calves have no effect on the rate of single and mixed infection with three intestinal protozoa.